Evaluar las diferentes combinaciones de aceites esenciales con mananoligosacaridos en la crianza de pollos broiler, en el cantón Marcabeli provincia El Oro. - Campoverde Tapia, Víctor Rolando (2018)
The present investigation it was done in the kanton of Marcabeli, in the region or El ORO; to evaluate different combinations of essential oils with mannologoccharides in raising broiler chickens as an alternative to antibiotic growth promoters, improve intestinal health and animal welfare. For this, 3600 chickens from the Cobb 500 line were used divided into four treatments. With there repetitions and 300 birds for each repetition. It was elevated: T1, Nutrifibe plus Selko pH, 300 grams of Nutrifibe, (organic promoter) per ton for birds up to 28 days; and 500 grams per ton for birds from to 29 to 49 days of age. Also it was used Selko pH in the water at 0.8cm per liter of water; T2, only Nutrifibe; T3 Selko pH plus APC, virginiamycin was added (antibiotic promotor) 500 grams per ton for birds from 1 to 49 days age, and in the water we added Selko pH from 0.8cm per Liter of water; and T4 it was used only virginiamycin. The study lasted 49 days, during which the highest food comsumption was T1 with 5324 grams. The best feed conversion was from T2 and T3 with 1, 84, the best pigmentation of T4 with a grade of 5, and the lowest mortality of T1 with 33%. In profitability the best reached. The T3 (APC plus Selko) with 40.60. Its conclude that T1 had a better performance in terms of productive parameters, which indicates that it can casily replace the antibiotics growth promoters (APC) Key words: Broiler chickens, Nutrifibe, Selko pH, APC